Posisi Duduk dan Lama Duduk di Depan Komputer sebagai Faktor Risiko Keluhan Nyeri Punggung Bawah pada Karyawan Kantoran - Ni Luh Putu Ekarini; Yulianti Putri Susman; Suratun Suratun; Nelly Yardes; Santa Manurung; Wartonah Wartonah (Poltekkes Kemenkes Jakarta III, 2023)
Background: Low back pain (LBP) is a feeling of pain around the lower back between the angles of the ribs to the tailbone. NPB complaints often occur in office employees who use computers in doing their work, where they use a static sitting position with a long interval of time. Complaints of LBP generally occur at the age of >35 years. Purpose: This study was to determine the relationship between age, sitting position and length of sitting in front of the computer with complaints of LBP in Lintasarta employees. Research Methods: Quantitative research with a cross sectional approach. The sampling technique used was purposive sampling with Chi Square data analysis. This research was conducted in February – May 2022 at PT Lintasarta. Results: The results of this study there was no significant relationship between age (p=0.853) and gender (p=1,000) with complaints of LBP and there was a significant relationship between sitting position (p=0.041) and length of sitting (p=0.033) in front of a computer with NPB complaints. Conclusion: The results of the chi square test found that there was no significant relationship between age, gender and complaints of LBP. There is a significant relationship between sitting position and long sitting in front of the computer with complaints of LBP. Recommendation: The role of nurses in handling complaints of NPB as advocates, educators, coordinators, counselors, and nursing care providers.